2009
DOI: 10.1002/pen.21586
|View full text |Cite
|
Sign up to set email alerts
|

Extension rheology of liquid-crystalline solution/layered silicate hybrids

Abstract: The extension rheology of polymer/layered silicate composites based on liquid-crystalline (LC) solution of hydroxypropylcellulose (HPC) in oligomeric polyethyleneglycole (PEG) was studied. The HPC concentration was 60 wt%. Extension experiments have been carried out for materials in the different phase states. Compositions containing Na-montmorillonite (MMT) were prepared by a two-stage method. Final systems may be attributed to solutions of HPC in PEG, which intercalates into MMT galleries. The ordered domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…The character of viscous response changes drastically when the temperature of experiment was lowered and the matrix becomes biphasic (LC + isotropic). It has been established that HPC/PEG demonstrates unusual rheological behavior for nematic or cholesteric systems 14, 22. This behavior consists in the significant viscosity rise when phase separation takes place and a LC phase appears.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The character of viscous response changes drastically when the temperature of experiment was lowered and the matrix becomes biphasic (LC + isotropic). It has been established that HPC/PEG demonstrates unusual rheological behavior for nematic or cholesteric systems 14, 22. This behavior consists in the significant viscosity rise when phase separation takes place and a LC phase appears.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior consists in the significant viscosity rise when phase separation takes place and a LC phase appears. In14 this behavior was explained as a result of reorganization of H‐bond network formed between terminal hydroxyl groups of PEG and the ones of hydroxypropyl groups in HPC macromolecules. In this case PEG molecules can act as both intradomain crosslinks and interdomain bridges.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the viscoelastic behavior of PEG-poly(lactic acid) composites showed that these materials could have a higher magnitude of storage modulus than pure polymers [60]. Another study showed the increase of viscosity due to loading additives in the biphasic polymer solution, which did not change in further growth of the filler concentration [61]. The addition of clay to PEG could change its Newtonian flow behavior to thixotropic shear thinning when its structure broke down by mechanical shearing, and its viscosity decreased with time under conditions of constant shear rate [62].…”
Section: Discussionmentioning
confidence: 99%